A review on the synthesis strategies and factors contributing to the formation of zeolitic imidazolate frameworks (ZIFs) and their applications - Mohamed Tahir, Mohamed Ibrahim; Abdullah, Abdul Halim; Raman, Velan; Md Yusof, Enis Nadia (Malaysian Analytical Sciences Society, 2024)
Zeolitic Imidazolate Frameworks (ZIFs) are a subclass of Metal-Organic Frameworks (MOFs) that have attracted significant attention due to their unique properties such as high surface area, tunable pore size, and excellent thermal and chemical stability. The review aims to discuss reported single and mixed-linker of ZIFs. The synthesis of ZIFs can be achieved through various methods such as solvothermal, hydrothermal, ionothermal, microwave-assisted, sonochemical, contra-diffusion synthesis, and mechanochemical. The review discusses the benefits and disadvantages of each method as well as a critical analysis of their effectiveness. The synthesis factors of ZIFs are classified into several types such as organic solvents, additives, concentration, temperatures, metal salt variations and the reaction time. Furthermore, the paper highlights several applications of ZIFs, including their impact on adsorption of pollutants, catalysis and drug delivery system. The paper concludes by summarising the recent advances in ZIFs research which leads to future directions for further research in this field.